Persistence of immune response to an adjuvanted varicella-zoster virus subunit vaccine for up to year nine in older adults - Tino F. Schwarz; Stephanie Volpe; Gregory Catteau; Roman Chlibek; Marie Pierre David; Jan Hendrik Richardus; Himal Lal; Lidia Oostvogels; Karlis Pauksens; Stephanie Ravault; Lars Rombo; Gerard Sonder; et al. (Taylor & Francis Group, 2018)
Background: In adults aged ≥60 years, two doses of the herpes zoster subunit vaccine (HZ/su; 50 µg varicella-zoster virus glycoprotein E [gE] and AS01B Adjuvant System) elicited humoral and cell-mediated immune responses persisting for at least six years. We assessed immunogenicity nine years post-initial vaccination. Methods: This open extension study (NCT02735915) followed 70 participants who received two HZ/su doses in the initial trial (NCT00434577). Blood samples to assess the cellular (intracellular cytokine staining) and humoral (ELISA) immunity were taken at year nine post-initial vaccination. Results: Participants' mean age at dose 1 was 72.3 years. The fold increases over pre-vaccination in the mean frequency of gE-specific CD4+ T-cells expressing ≥2 activation markers plateaued from year four post-dose 1 until year nine. Anti-gE antibody geometric mean concentrations plateaued and remained above pre-vaccination levels from year four onwards. Immunogenicity at year nine was similar across age strata (60-69, ≥70 years) and confirmed statistical prediction model results using data for up to year six. Further modeling using all data up to year nine predicted immune responses would remain above the pre-vaccination level up to year 15. Conclusion: In adults aged ≥60 years, HZ/su-induced immunogenicity remained above pre-vaccination levels for at least nine years post-initial vaccination. Summary: After vaccination with HZ/su, both cell mediated and humoral immunity remained above pre-vaccination levels up to year 9 regardless of age group. Immune responses are predicted to remain above baseline up to 15 years post initial vaccination.